THE RELATIONSHIP BETWEEN ANTHROPOLOGY AND PSYCHOLOGY IN THE PERSPECTIVE OF THE QURAN: Hubungan Antara Antropologi dan Psikologi di dalam Perspektif Al-Quran - Sri Ahadah Nuril Fajar; Aisyatur Rahmah Wiwana (Yayasan Salam Cerdas Al-Fattah, 2023)
Humans are an important object on this earth. Humans are the most special creatures created by Allah SWT. Humans were created in this world for nothing other than to worship Allah SWT. Every human being has its own characteristics, starting from the type of male and female, body shape, ethnicity, skin, color, race and other ethnicities. All of these are studies that will be discussed in anthropological studies. Apart from that, Allah has destined us to live in this world with different fates, some have good lives, some have bad ones, but all of them will definitely be delicious when we live this life full of gratitude. With these diverse circumstances, humans have different attitudes and also different psychological conditions. The significant differences that exist between humans and each other require us to respect each other. This aims to enable us to live our lives peacefully, safely and peacefully. This journal was written using qualitative methods that develop discussion from various existing sources. So at the core of anthropology and psychology there is a discussion about humans who have enormous diversity, we as humans must understand and respect the differences that exist in all of us.